The Effect of E-Recruitment and Equal Employment Opportunity on Employee Performance In The Indonesian Banking Industry - Yusniaulia, Agny Nadya; Sary, Fetty Poerwita (Universitas Pamulang, 2023)
An organization has to be aware about the factors that influence employee performance, because that can affect overall organizational performance. This study aims to analyze how employee performance in the Indonesian banking industry view from e-recruitment processing and Equal Employment Opportunity (EEO), the effect on that factor to employee performance simultaneously and partially evaluated. The method is a quantitative researches by distributing questionnaires to 100 employees of the Indonesian banking industry. Data processing was carried out using descriptive statistical analysis techniques and Structural Equation Model (SEM) - Partial Least Square (PLS) technique through SmartPLS 3. As stated by data processing that has been done, there is no significant effect of E-Recruitment (X1) on employee performance (Y) in the banking industry in Indonesia, there is a significant effect between Equal Employment Opportunities (X2) on Employee Performance (Y) in the Banking Industry in Indonesia, the E-Recruitment and Equal Employment Opportunity variables (EEO) has an effect to employee performance (Y) in the Indonesian banking industry simultaneously and partially. This is indicated by the resulting Fh value of 24.366 and Ft of 3.090 or Fh > Ft